A Psychoanalysis on Internal Conflict of Bruce Wayne as Seen in Matt Reeves’ The Batman (2022) Movie - Muhammad Afra Masyhur; Muhammad Fithratullah; E. Ngestirosa Endang Woro Kasih (Universitas Teknokrat Indonesia, 2023)
People need to learn about the causes of internal conflict; people need to be aware of experiencing it. Unresolved inner conflict is a major cause of aggression, anger, apathy, and passivity. Emotional discomfort and self-sabotage are specifically related to internal conflict. This research aims to figure out the representation of internal conflict and the causes of internal conflict in Bruce Wayne's character in The Batman (2022) movie. This study applied a psychological approach from Sigmund Freud. The representation theory by Stuart Hall was applied to reveal the representation of internal conflict in the Bruce Wayne character. It was also supported by personality theory by Barbara Engler to determine the type of internal conflict and the theory of internal conflict by Peter Michaelson to determine the causes of internal conflict. This study applied a descriptive qualitative method. The data were a picture, dialogue, and narration, and the data source was from The Batman (2022) movie. The result reveals avoidance-avoidance conflict caused by Bruce's inability choosing to keep being Batman. He destroys himself or stops and leaves Gotham in ruin. Double approach-avoidance is caused by Bruce's inability to choose whether Riddler's method is right or wrong. The revelation from The Riddler causes approach avoidance. Bruce has two choices: not being Batman or continuing to be Batman to make his father proud.